Wood waste-based functionalized natural hydrochar for the effective removal of Ce(III) ions from aqueous solution (2023)
In this study, a sustainable and easily prepared hydrochar from wood waste was studied to adsorb and recover the rare earth element cerium (Ce(III)) from an aqueous solution. The results revealed that the hydrochar contains several surface functional groups (e.g., C–O, C = O, OH, COOH), which largely influenced its adsorption capacity. The effect of pH strongly influenced the Ce(III) removal, achieving its maximum removal efficiency at pH 6.0 and very low adsorption capacity under an acidic solution. The hydrochar proved to be highly efficient in Ce(III) adsorption reaching a maximum adsorption capacity of 327.9 mg g−1 at 298 K. The kinetic and equilibrium process were better fitted by the general order and Liu isotherm model, respectively. Possible mechanisms of Ce(III) adsorption on the hydrochar structure could be explained by electrostatic interactions and chelation between surface functional groups and the Ce(III). Furthermore, the hydrochar exhibited an excellent regeneration capacity upon using 1 mol L−1 of sulfuric acid (H2SO4) as eluent, and it was reused for three cycles without losing its adsorption performance. This research proposes a sustainable approach for developing an efficient adsorbent with excellent physicochemical and adsorption properties for Ce(III) removal.